2011
DOI: 10.1159/000326899
|View full text |Cite
|
Sign up to set email alerts
|

Anemia of Chronic Disease in Chronic Obstructive Pulmonary Disease: A Case-Control Study of Cardiopulmonary Exercise Responses

Abstract: Background: Anemia may be present in patients with chronic obstructive pulmonary disease (COPD) and further impair their functional capacity. Objectives: This study investigated the prevalence of anemia of chronic disease (ACD) in COPD patients and its impact on dyspnea and exercise capacity, utilizing cardiopulmonary exercise testing (CPET). Methods: ACD prevalence was assessed in 283 consecutive patients with stable COPD (263 males, 60 females; age 60.31 ± 5.34 years; percent forced expiratory volume in 1 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 75 publications
6
52
0
1
Order By: Relevance
“…One report 10 studied iron status in a marginal number of nonanaemic COPD patients, and two additional studies only studied iron deficiency in COPD patients with anaemia. 11,12 Moreover, to our knowledge, no previous studies have addressed the effects of endurance training in chronic patients suffering from NAID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One report 10 studied iron status in a marginal number of nonanaemic COPD patients, and two additional studies only studied iron deficiency in COPD patients with anaemia. 11,12 Moreover, to our knowledge, no previous studies have addressed the effects of endurance training in chronic patients suffering from NAID.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In contrast, in patients with chronic obstructive pulmonary disease (COPD), iron deficiency has only been studied in the context of anaemia. [10][11][12] Patients with COPD often show oxygen delivery impairment during exercise. Moreover, skeletal muscle dysfunction is a well recognized systemic effect of the disease that can be associated to abnormal mitochondrial oxygen utilization.…”
Section: Introductionmentioning
confidence: 99%
“…31 Anaemia of chronic disease occurs in about 10% of patients with COPD and is associated with worse quality of life and impaired survival. 32 …”
Section: Other Problemsmentioning
confidence: 99%
“…This was mild anemia which is similar to the previous studies. [6,18,19] In our present study, anemia defined by Hct <39% in males and <36% in females. We found that anemia was present in 25.6% of males and 34.2% of females which is higher than the findings of Chambellan et al where they reported that 13% of males and 8% females were anemic.…”
Section: Discussionmentioning
confidence: 43%
“…The trend was not the same in female patients. Maximum female patients were anemic (Hb <12) in 71-80 age group (23, 11.1%) followed by 61-70 years (19,9.2%) as shown in Table 2.…”
Section: Resultsmentioning
confidence: 93%